2007
DOI: 10.1007/s00431-007-0568-y
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected finding in a child with neurological problems: mosaic ring chromosome 18

Abstract: Major neurological disorders may accompany rare chromosomal abnormalities. As an example of this rare condition, we present a case with microcephaly, mental retardation, developmental delay, hyperactivity, stereotypic movements, seizures and dysmorphic facial appearance in whom a mosaic ring chromosome 18 was found [45,XX,-18/46,XX,r(18)/46,XX,dicr(18)]. Although ring chromosome 18 phenotype has been known for a long time, this is the third reported patient with a dicentric ring chromosome 18 mosaicism. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…P119’s karyotype was identified as 46,XX,del(18)(q21.3)/46,XX,r(18)(p11.32q21.3)/45,XX,-18, all with loss of the MBP region ( Fig 3 ). However, it has been reported that a patient with a karyotype of 45,XX,-18/46,XX,r(18)(p11.3q23)/46,XX,dicr(18)(p11.3q23;p11.3q23), which indicated a loss of MBP , showed normal brain MRI findings[ 88 ], suggesting the hypomyelination was the result of a joint effort of many genes together in the fragment lost, not only MBP. In the presenting study, besides MBP , 46,XX,del(18)(q21.3) caused the loss of 16 morbid genes including NEDD4L , MALT1 , RAX , LMAN1 , CCBE1 , MC4R , PIGN , TNFRSF11A , BCL2 , SERPINB7 , SERPINB8 , RTTN , CYB5A , TSHZ1 , CTDP1 , TXNL4A , and 46,XX,r(18)(p11.32q21.3) were caused additional loss of LPIN2 and SMCHD1 .…”
Section: Discussionmentioning
confidence: 99%
“…P119’s karyotype was identified as 46,XX,del(18)(q21.3)/46,XX,r(18)(p11.32q21.3)/45,XX,-18, all with loss of the MBP region ( Fig 3 ). However, it has been reported that a patient with a karyotype of 45,XX,-18/46,XX,r(18)(p11.3q23)/46,XX,dicr(18)(p11.3q23;p11.3q23), which indicated a loss of MBP , showed normal brain MRI findings[ 88 ], suggesting the hypomyelination was the result of a joint effort of many genes together in the fragment lost, not only MBP. In the presenting study, besides MBP , 46,XX,del(18)(q21.3) caused the loss of 16 morbid genes including NEDD4L , MALT1 , RAX , LMAN1 , CCBE1 , MC4R , PIGN , TNFRSF11A , BCL2 , SERPINB7 , SERPINB8 , RTTN , CYB5A , TSHZ1 , CTDP1 , TXNL4A , and 46,XX,r(18)(p11.32q21.3) were caused additional loss of LPIN2 and SMCHD1 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a cryptic deletion may be the basis of the phenotypic abnormalities in apparently complete rings, such as the deletion of the IGF1R gene at 15q26.3 in a ring 15. Also, the phenotypic variability seen in patients with similar ring chromosomes may be a consequence of their instability and of the variation in gene dosage of each cell (Hecht, 1969;Palmer et al, 1977;Zuffardi et al, 1980;Knijnenburg et al, 2007;Rossi et al, 2008a), as for instance in the patient with a ring 18 reported by Koç et al (2008) who showed partial trisomy 18 in a considerable number of cells, due to the formation of dicentric rings, which resulted in a more severe phenotype. Rossi et al (2008a) described a patient with a ring 13 who had a deletion and a duplication of approximately 6 Mb each, oligohydramnios and cystic kidney, features that were attributed to trisomy 13.…”
Section: Introductionmentioning
confidence: 99%
“…In general, clinical phenotypes of patients with ring chromosomes may be related with different factors, including gene haploinsufficiency, gene duplications, ring instability and level of mosaicism [ 6 , 7 ]; also, loss of ring chromosomes may lead for some chromosomes to mosaic karyotypes with 45 chromosomes [ 14 ]. The proband under report presented with primary observation of small head size and facial dysmorphism.…”
Section: Discussionmentioning
confidence: 99%